PRACTICES OF RELIGIOUS MODERATION AMONG MADURESE MIGRANTS IN BALI - Sa’diyah, Halimatus; Hasanah, Uswatun (Islamuna: Jurnal Studi Islam, 2025)
ABSTRACT Harmony between religious communities is the main foundation for the application of religious moderation in the midst of a multicultural society in order to be able to display a peaceful and harmonious life. The Madurese people who migrated to Bali seem to be able to adapt to the people in Bali who are Hindu and Buddhist. Even though the people of Madura are famous for being fanatical about Islam. This study aims to analyze the religious moderation attitude of Madurese migrants in Bali. This study uses a qualitative approach. The data was obtained from the results of field observations, interviews, and documentation. The data analysis techniques carried out in this study are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the attitude of religious moderation of Madurese migrants in Bali is manifested by the attitude of tolerance between fellow believers of Islam in Bali as well as between followers of Islam and Hinduism in Bali which can be seen during the celebration of Indonesian Independence Day and the implementation of traditional ceremonies in Bali. The role of Muslim leaders in maintaining the attitude of religious moderation of Madurese Nomads in Bali as mediators and facilitators in interfaith dialogue activities in Bali. The results of this study have significant implications for the development of Islamic Studies studies, especially in the context of Nusantara Islam, religious moderation, and religious relations with local culture. ABSTRAK Kerukunan antar umat beragama merupakan landasan pokok pada penerapan moderasi beragama di tengah masyarakat yang multikultural agar mampu menampilkan kehidupan yang damai dan harmonis. Masyarakat Madura yang merantau di Bali nampaknya mampu beradaptasi dengan masyarakat di Bali yang beragama Hindu dan budha. Padahal masyarakat Madura terkenal fanatik dengan agama Islam. Penelitian ini bertujuan untuk menganalisis sikap moderasi beragama perantau Madura di Bali. Penelitian ini menggunakan pendekatan kualitatif. Data-data diperoleh dari hasil observasi lapangan, wawancara, dan dokumentasi. Teknik analisis data yang dilakukan dalam penelitian ini yaitu pengumpulan data, reduksi data, penyajian data dan penarikan Kesimpulan. Hasil penelitian menunjukkan bahwa Sikap moderasi beragama perantau Madura di Bali diwujudkan dengan sikap toleransi antar sesama pemeluk agama Islam di Bali maupun antar pemeluk agama Islam dan Hindu di Bali yang dapat dilihat pada saat perayaan Hari Kemerdekaan RI dan pelaksanaan upacara adat di Bali. Peran tokoh muslim dalam menjaga sikap moderasi beragama Perantau Madura di Bali sebagai mediator dan fasilitator dalam kegiatan dialog antar agama di Bali. Hasil penelitian ini memiliki implikasi signifikan terhadap pengembangan kajian Studi Islam, khususnya dalam konteks Islam Nusantara, moderasi beragama, dan relasi agama dengan budaya lokal.